Biological Meshes for Inguinal Hernia Repair – Review of the Literature - Köckerling, Ferdinand; Alam, Nasra N.; Narang, Sunil K.; Daniels, Ian R.; Smart, Neil J. (Frontiers in Surgery, 2015)
Introduction Biological meshes are a potential alternative to the synthetic meshes to avoid complications and in a contaminated field for incarcerated inguinal hernias. The clinical experiences gained with biological meshes for repair of inguinal hernias are presented in this review. Material and Methods In a literature search of the Medline database using the key word “Biological mesh” 2,277 citations were found. There remained seven studies and two abstracts in which biological meshes had been used to repair inguinal hernias. Results In prospective, randomized trials the use of polypropylene vs biological meshes was compared in open inguinal hernia repair. There was no difference in the recurrence rate, but in the postsurgical pain incidence in favor of the biological mesh. In the remaining retrospective studies the recurrence rates were also acceptable. The biological mesh was used successfully in a potentially contaminated setting. Conclusion Inguinal hernias can be repaired with biological meshes with reasonable recurrence rate, also as an alternative in a potentially contaminated field.